Lianas of UiTM Forest Reserve / Suhaini Ali - Ali, Suhaini (2000)
The Reserve Forest of Universiti Teknologi MARA Pahang, became as protected forest which was gazatted for the Universiti Teknologi MARA students. The various species in this lowland Forest Reserve was been caught attention by a group of student from Diploma In Wood Industry, Universiti Teknologi MARA Pahang for their final project. The final project is about Lianas or woody climbers' families and their commercial value. The survey plot is about 50m x 50m with the percentage of it 0.05 % from the whole areas of Universiti Teknologi MARA Forest Reserve. There are more then six species or families of Lianas was found in Universiti Teknologi MARA Pahang Forest Reserve of Line 11 from our survey data.